Synthesis and properties of a novel alkylselenium substituted phthalocyanine - Ezquerra Riega, Sergio Dario (2015)
The preparation and characterization of a tetrasubstituted alkylselenium zinc(II) phthalocyanine are reported herein for the first time. The precursor 4-(butylselanyl)phthalonitrile (4) was obtained in 65% yield. Tetrasubstituted alkylselenium zinc(II) phthalocyanine 5 was synthesized from 4 and zinc acetate in the presence of 1,8-diazabicyclo[5.4.0]undec-7-ene in butanol.